A126 ONCE IS BY CHANCE, TWO IS A TREND: A RECURRING FINDING WITHIN THE POST-RESECTION DEFECT. (21st February 2022) - Alshihry, I A; Tomaszewski, M; Shahidi, N C
Abstract: Background: A 74-year-old male was referred for the management of a large non-pedunculated colorectal polyp in the transverse colon. On optical evaluation, including high-definition white-light and narrow-band imaging (NBI), a 30mm 0-IIA non-granular large non-pedunculated colorectal polyps (LNPCP) was identified with optical features in keeping with adenomatous histopathology (NBI International Colorectal Endoscopic II, Japan NBI Expert Team IIA, Kudo Pit Pattern III/IV). Endoscopic mucosal resection (EMR) was performed. During sequential tissue transection and evaluation of the expanding submucosal defect a hole with a surrounding white-cautery ring was identified in keeping with significant deep mural injury. However, on careful evaluation a cystic structure was identified with a viscous amorphous substance emanating from it. Endoscopic resection of the lesion was completed with subsequent through-the-scope mechanical clip closure of the area of concern. Aims: case report showing unique finding of intra-cellular mucin emanating from the post-resection defect has been identified as a potential intra-procedural finding of a mucinous adenocarcinoma Methods: Endoscopic mucosal resection of a mid transverse colon polyp Results: Histopathology identified a villous adenoma with high-grade dysplasia with submucosal mucin and an indeterminate focus of carcinoma; highly suspicious for a mucinous adenocarcinoma. No muscularis propria was identified. After multi-disciplinary review, the patient underwent laparoscopic right hemicolectomy with no evidence of invasive disease. Conclusions: Recently coined as the "fish-eye" polypectomy defect, intra-cellular mucin emanating from the post-resection defect has been identified as a potential intra-procedural finding of a mucinous adenocarcinoma; specifically, in an otherwise benign appearing LNPCP based on real-time optical evaluation. Herein we describe the second case in the literature. This reinforces the importance of meticulous evaluation of the post-resection defect to stratify this finding from deep mural injury. Moreover, further understanding of the clinical ramifications of this unique intra-procedural finding is needed. Funding Agencies: None